CONTENT ANALYSIS OF SOCIAL MARKETING CONTENT ON #DAURULANG HASHTAG USERS ON INSTAGRAM - Dewi Sani Sukma; Ujang Sumarwan (Journal of Child, Family, and Consumer Studies, 2023)
The fact that a lot of paper waste has accumulated is the reason for the #Daurulang social marketing movement to tackle this problem. The purpose of this research is to identify and evaluate social marketing content messages to users of the hashtag #Daurulang on Instagram. This research is an exploratory design with a content analysis method. The data collection technique used a purposive sampling technique for 200 social campaign contents on Instagram using the content analysis method. Data were processed by cross-tabulation and descriptive interpretation using Microsoft Excel, IBM SPSS 25.0, and Voyant applications as supporting applications for processing qualitative data. The results of the analysis show that the effectiveness of messages from most of the content is considered interesting, uses standard language to make it easier to understand, includes two necessary pieces of information, raises awareness or sympathy, and is considered to have the potential to change reader behavior. Content readers are expected to be able to choose and read content wisely and apply the good things they get to reduce paper waste production.